Suppressing the cytotoxicity of CuO nanoparticles by uptake of curcumin/BSA particles. Issue 18 (21st April 2016) - Zhang, Wenjing; Jiang, Pengfei; Chen, Ying; Luo, Peihua; Li, Guanqun; Zheng, Botuo; Chen, Wei; Mao, Zhengwei; Gao, Changyou
Abstract : Curcumin/BSA particles could suppress the cytotoxicity generated by CuO nanoparticles as a result of decrease of both the intracellular reactive oxygen species (ROS) level and Cu 2+ concentration, while the free curcumin did not show any obvious detoxicating effect. Abstract : The adverse effects of metal-based nanoparticles on human beings and the environment have received extensive attention recently. It is urgently required to develop a simple and effective method to suppress the toxicity of metal-based nanomaterials. In this study, a hydrophobic antioxidant and a chelation agent curcumin (CUR) were encapsulated into bovine serum albumin (BSA) particles by a simple co-precipitation method, and followed by glutaraldehyde cross-linking. The CUR/BSA particles had an average size of 300 nm in diameter with a negatively charged surface and sustained curcumin release properties. The cellular uptake and cytotoxicity of CUR/BSA particles were followed on A549 cells, HepG2 cells and RAW264.7 cells. The CUR/BSA particles had higher intracellular accumulation and lower cytotoxicity compared with the free curcumin at the same drug concentration. The CUR/BSA particles could suppress the cytotoxicity generated by CuO nanoparticles as a result of decrease of both the intracellular reactive oxygen species (ROS) level and Cu 2+ concentration, while the free curcumin did not show any obvious detoxicating effect. The detoxicating effects of CUR/BSA particles were further studied in an intratracheal instillation model in vivo, demonstrating significant reduction of toxicity and inflammatory response in rat lungs induced by CuO nanoparticles. The concept-proving study demonstrates the potential of the CUR/BSA particles in suppressing cytotoxicity of metal-based nanomaterials, which is a paramount requirement for the safe application of nanotechnology.